Implementation of the Sanitation Clinic in Health Center in Kupang (Study at Oebobo, Oepoi, and Bakunase) - Taebenu, Dian Kristiyanti; Salmun, Johny A. R.; Sahdan, Mustakim (Faculty of Public Health, Nusa Cendana University, 2023)
Sanitation clinic is one of the services at the puskesmas that integrates curative, promotive, and preventive efforts which have roles, among others, as an information center, a referral center for facilitators in the field of environmental health and environmental-based diseases. This study was conducted to determine the description of the implementation of the sanitation clinic of the puskesmas in the city of Kupang which includes operational policies, implementation of activities, resources for the sanitation clinic of the puskesmas in the city of Kupang. The research method used is descriptive with a survey approach, which is a study conducted to describe a phenomenon that occurs in society. The population in this study is all 6 sanitation clinic officers working at sanitation clinics. The analysis used is univariate analysis. The result of the study show that 3 puskesmas in Kupang City that run sanitation clinic activities use the Regulation of the Minister of Health No. 13 of 2015.The implementation of sanitation clinics in 3 puskesmas has carried out sanitation clinic activities inside the building and outside the building. Resources for sanitation clinic activities in terms of the availability of personnel implementing facilities and infrastructure and funding sources are quite good. It is recommended for the Health office to carry out special trainning for staff implementing sanitation clinic activities at puskesmas and suggestion for Puskesmas to carry out socialization of clinical activities to cross programs in the Puskesmas so that they have the same undrstanding.